Effectiveness of some integrated disease management factors (IDM) on Fusarium wilt infected tomato - Salim, Hussein Ali; Simon, Sobita; Lal, Abhilasha A.; Abdulrahman, Abbas Lateef (Journal of Scientific Agriculture, 2017)
The study was conducted to investigate efficacy of Integrated disease management (IDM) viz., solarized soil, Trichoderma harzianum, spent mushroom compost and carbendazim on growth characteristics of infected tomato by Fusarial wilt (Fusarium oxysporum f.sp. lycopersici) under pots conditions in the Bio-net house during 2013-2014. Seven treatments and five replicates were taken up in completed randomized design. Maximum shoot length, fresh and dry shoot weight were noticed in T4 (solarized soil+ Spent mushroom compost+ T. harzianum) 118.10 cm, 67.25 and 42.20 g respectively as compared to T. harzianum or spent mushroom compost that alone treated plants. Maximum root length, fresh and dry root weight were also recorded in T4 (solarized soil+ spent mushroom compost+ T. harzianum) 28.35 cm, 4.65 and 2.55 g respectively. The yield of tomato plants was significantly increased in T6 (tomato plant alone without Fusarium oxysporum) 170.15 g/plant followed by T4 137.52 g/plant as compared with T0- Fusarium oxysporum alone and T1- Solarized soil + Fusarium oxysporum 0.0 g.